The Evolution of Healthcare Economics: Blockchain Integration Amidst Medicare Reform - Wright, Ryan (Blockchain in Healthcare Today, 2025)
As healthcare institutions face Medicare funding challenges, blockchain technology offers solutions for financial stability and improved patient care. This paper examines how decentralized systems create new revenue streams while addressing transparency and efficiency, highlighting the convergence of traditional healthcare with network states and emerging technologies.